Matrix-assisted laser desorption/ionization mass spectrometry imaging analysis revealed the spatial distribution of metabolites during Ziziphi Spinosae Semen at different growth periods - Zhao, Mengwei; Liu, Zhao; Wang, Jiemin; Liu, Yuting; Yan, Yuping; Liu, Ning; Jiang, Jianming; Song, Yongxing; Sun, Huigai; Ma, Donglai (Frontiers in Plant Science, 2025)
Ziziphi Spinosae Semen (ZSS), a medicinal food, is one of the most popular Chinese medicinal herbs, known for its rich bioactive ingredients, such as terpenoids and flavonoids. The content of these bioactive ingredients in ZSS varies with age. However, the distribution of these bioactive ingredients throughout the developmental phases of ZSS—white maturity (S1), firm ripening (S2), and full ripening (S3)—and within specific tissues like the cotyledon, endosperm, and radicle, has not yet been determined. This research aimed to analyze the spatial distribution of key quality markers in ZSS and elucidate the metabolite quality characteristics throughout its growth stages. Utilizing matrix-assisted laser desorption/ionization-mass spectrometry imaging (MALDI-MSI), 25 bioactive ingredients were identified and visualized in ZSS, including three terpenoids, seven flavonoids, four alkaloids, and eleven amino acids. The MALDI images revealed distinct spatial variations in the distribution of these bioactive ingredients across different regions of ZSS tissues and different growth stages. Moreover, as ZSS matured, the distribution area of specific bioactive ingredients significantly increased, encompassing three terpenoids, six flavonoids, two alkaloids, and seven amino acids. Utilizing ion imagery, Principal Component Analysis (PCA) coupled with Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) effectively differentiated samples from various developmental periods. Additionally, nine major bioactive ingredients were identified as potential quality markers for ZSS. This research demonstrates that the content and distribution of bioactive components in ZSS change during growth. The analysis provided by MALDI-MSI offers an experimental basis for understanding the accumulation and distribution of bioactive components during the maturation of ZSS.